Evaluation of the Effect of Andrographolide on Atherosclerotic Rabbits Induced by Porphyromonas gingivalis. (18th August 2014) - Al Batran, Rami; Al-Bayaty, Fouad; Al-Obaidi, Mazen M. Jamil; Hussain, Saba F.; Mulok, Tengku Z.
Abstract : Epidemiologic evidence has demonstrated significant associations between atherosclerosis and Porphyromonas gingivalis ( Pg ). We had investigated the effect of andrographolide (AND) on atherosclerosis induced by Pg in rabbits. For experimental purpose, we separated thirty male white New Zealand rabbits into 5 groups. Group 1 received standard food pellets; Groups 2–5 were orally challenged with Pg ; Group 3 received atorvastatin (AV, 5 mg/kg), and Groups 4-5 received 10 and 20 mg/kg of AND, respectively, over 12 weeks. Groups treated with AND showed significant decrease in TC, TG, and LDL levels (P < 0.05 ) and significant increase in HDL level in the serum of rabbits. Furthermore, the treated groups (G3–G5) exhibited reductions in interleukins (IL-1 β and IL-6) and C-reactive protein (CRP) as compared to atherogenicgroup (G2). The histological results showed that the thickening of atherosclerotic plaques were less significant in treated groups (G3–G5) compared with atherogenicgroup (G2). Also, alpha-smooth muscle actin ( α -SMA) staining decreased within the plaques of atherogenicgroup (G2), while it was increased in treated groups (G3–G5). Lastly, groups treated with AV and AND (G3–G5) showed significant reduction of CD36 expression (P < 0.05 ) compared to atherogenicgroup (G2). These results substantially proved that AND contain antiatherogenic activity.